Engineering Tolerance: Systematic Management of Hidden Curriculum in a Holistic 24-Hour Educational Ecosystem - Syarifah Syarifah; Mohammad Muslih; Saiful Anwar; Samsirin Samsirin; Nurul Azizah (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2026)
While tolerance is often treated as a pedagogical goal within Classroom settings, the systemic mechanisms through which educational institutions engineer holistic environments to foster such values remain underexplored. This study aims to examine how tolerance is systematically engineered as an emergent institutional outcome through the management of a 24-hour educational ecosystem at Pondok Modern Darussalam Gontor. Employing an ethnographic research design, the study involved six months of prolonged field immersion, encompassing 200 hours of participant observation, in-depth interviews with 10 key informants, ranging from leadership to students, and extensive document analysis. The findings reveal that tolerance at this institution is not merely a spontaneous cultural trait but a sophisticated, managed achievement produced through a structured social architecture. This process is sustained by a systematically managed hidden curriculum that translates foundational values into robust governance structures, peer-led conflict resolution, and intentional cross-regional social mixing. The study further identifies a tension between behavioral compliance and deep internalization, highlighting a potential durability gap in value resilience beyond institutional boundaries. It is concluded that character formation is most effective when the institution itself functions as the primary curriculum, mechanically integrating formal policy with everyday social practices. By reframing tolerance as an institutional management output, this research provides a novel framework for stakeholders to move beyond doctrinal teaching toward building resilient, value-based educational ecosystems. Future research should prioritize longitudinal studies to examine the long-term sustainability of such institutionally scaffolded competencies in unregulated social environments.